(3OjhGf eMeO GdegOj GdWHGWHGFjs - (3GHf GdeQJVj , eMeO egOj Hf eQJVj Hf eMeO GdWHGWHGFj GdHQh LQOj,J (B1212 (3g` s ((3eMeO UGOb Hf GdMSf s)
(3ChdgG (B:s
(3bGd WGH KQGg aj QKGA GdMSjf(B: (3TGA ef GdfGS dGfGS hdG TGA ghJ Hge aj egGhj GdZj CghGA s
(3BNQgG (B:s
(3gPG KfGFj Mjf LGT LjTj hEf hUa GdYjT fUa GdYjT s
(3jdj GdOjhGf edMb Hg hjMJhj Ydi hQbJGf ef TYQ GdTGYQs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B334 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B61s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B205 s
Keywords: (3GdCOHs